Assessment of Group Dynamics among Fisherwomen Self Help Groups: A Participatory Monitoring Approach - Nikita Gopal; J. Charles Jeeva; R. Parvathy and M. Nasser (Journal of Global Communication, 2010)
Self Help Groups can be used as an important medium for the implementation of development programmes. The formation of the group is usually facilitated by the implementing agencies. It can be a spontaneous or a purposive exercise. However, the cohesiveness of a group and its internal dynamics is important for successful implementation of planned initiatives. As part of the National Agricultural Innovation Project being operated by Central Institute of Fisheries Technology in the small pelagics sector in Cochin, Kerala, fisherwomen were organized into self help groups (post harvest activity clusters). The exercise was a planned one and the final group formation purposive. After the formation of groups, the group dynamics was assessed using H-form, a participatory monitoring approach. The relationship between the socio-economic variables and group dynamics was also examined. This paper presents the results of the assessment.